Longitudinal assessment of nonavalent vaccine HPV types in a sample of sexually active African American women from ten U.S. Cities. Issue 34 (9th August 2021) - Madhivanan, P.; Krupp, K.; Coudray, M.; Colbert, B.; Ruiz-Perez, D.; Cui, H.; Bokulich, N.; Narasimhan, G.; Mathee, K.; Cook, R.L.; Schwebke, J.; Roe, D.
Abstract: Background: Chronic infection with high-risk human papillomavirus is a necessary cause for cervical carcinogenesis. This study examined prevalence of nonavalent vaccine preventable HPV types over four months among sexually active women in the United States. Methods: This sub-study obtained meta-data for 80 of the 1, 365 women (18–25 years), enrolled in the BRAVO study, a randomized, open-label trial of home screening and treatment of asymptomatic bacterial vaginosis at high-risk for sexually transmitted infections conducted between 2008 and 2013. Participants were randomized to treatment or standard-of-care, and followed every 2-months for 12 months. Stored vaginal swabs from the first three visits were tested for the nine vaccine preventable HPV types using quantitative PCR. Prevalence and associated 95% confidence intervals for the HPV types were assessed using R (version 3.6.1). Results: The average age of the participants was 21.5 (SD ± 2.11) years, with 60% having ever been pregnant and all were African-American. Majority (71%) reported ≥ two sex partners in the prior year with 89% having unprotected vaginal sex and 45% having a new sex partner in the prior year. About 30% had ≥ one of the nine nonavalent vaccine HPV types at all three time points over a period of four months, 15% at two of any three visits, 19% at one of the three visits and 36% were negative for all nine vaccine HPV types at all time points. The most frequently detected HPV vaccine types were 52, 58, 16, and 18. The prevalence of any vaccine HPV types, and high-risk HPV types was 63.8% and 58.8%, respectively. Conclusions: Our findings suggest that HPV vaccination which is currently recommended for all unvaccinated persons through age 26 years, is likely to be more beneficial than previously thought as nonavalent HPV vaccine was not available during the time these data were collected.